Observation of top quark pairs produced in association with a vector boson in pp collisions at root s=8 TeV - Khachatryan, V. (2016)
Measurements of the cross sections for top quark pairs produced in association with a W or Z boson are presented, using 8 TeV pp collision data corresponding to an integrated luminosity of 19.5 fb(-1), collected by the CMS experiment at the LHC. Final states are selected in which the associated W boson decays to a charged lepton and a neutrino or the Z boson decays to two charged leptons. Signal events are identified by matching reconstructed objects in the detector to specific final state particles from t (t) over barW or t (t) over barZ decays. The t (t) over barW cross section is measured to be 382(-102)(+117) fb with a significance of 4.8 standard deviations from the background-only hypothesis. The t (t) over barZ cross section is measured to be 242(-55)(+65) fb with a significance of 6.4 standard deviations from the background-only hypothesis. These measurements are used to set bounds on five anomalous dimension-six operators that would affect the t (t) over barW and t (t) over barZ cross sections.